(untitled) - Holtzblatt, Karen (San Francisco, 2005)
Rapid Contextual Design provides detailed suggestions on structuring the project and customer interviews, conducting interviews, and running interpretation sessions. The handbook walks you step-by-step through organizing the data so you can see your key issues, along with visioning new solutions, storyboarding to work out the details, and paper prototype interviewing to iterate the design—all with as little as a two-person team with only a few weeks to spare!
Keywords: System design,System analysis